FLIGHT FROM PERSECUTION AS IMITATION OF CHRIST: LACTANTIUS' DIVINE INSTITUTES IV. 18, 1–2 - Nicholson, Oliver (The journal of theological studies, 1989)
OLIVER NICHOLSON; FLIGHT FROM PERSECUTION AS IMITATION OF CHRIST: LACTANTIUS' DIVINE INSTITUTES IV. 18, 1–2*, The Journal of Theological Studies, Volume 40, Iss